Pengaruh Social Media Marketing terhadap Purchase Intention dengan Brand Image sebagai Variabel Intervening: (Studi Kasus pada Konsumen Kopi di Jabodetabek) - Mita Oktaviani; Ika Febrilia; Rahmi Rahmi (Universitas 45 Surabaya, 2025)
The purpose of this research is to determine the influence of social media marketing on purchase intention with brand image as an intervening variable. The data collection method used in this study was a survey conducted by distributing questionnaires created through Google Form. The research sample consisted of 203 respondents from Jabodetabek area, aged 17 years or older, and familiar with Tuku Coffee Shop. The data analysis used to process and analyze the research results was Structural Equation Modeling (SEM) with AMOS to analyze. The results of this study indicate that social media marketing has an effect on brand image, brand image has an effect on purchase intention, social media marketing has an effect on purchase intention, and social media marketing has an effect on purchase intention through brand image.